Positive Selection in Zinc Finger Protein Reveals Genetic Signatures of Adaptive Evolution in Undifferentiated Stem Cells during Evolution in Mammals - Ali, Mahboob; Khan, Palwasha; Mahmood, Mahreen; Han, Jilong; Afzal, Gulnaz; Qadeer, Iram; Azmal, Syed Ali; El-Mouhty, Nadia R. A.; Mahmoud, Samy F.; Jafri, Ibrahim; Ali, Muhammad; Hashmi, Nighat (Journal of Zoological Systematics and Evolutionary Research, 2023)
Positive selection refers to the process by which certain genetic variations are more likely to be passed on to future generations because they confer some advantage in terms of survival or reproduction. Zinc finger proteins are a type of transcription factor that plays a role in regulating gene expression, particularly in undifferentiated stem cells. Suppose it has been found that certain zinc finger proteins show genetic signatures of positive selection in mammals. In that case, it suggests that these proteins may have played a role in adaptive evolution in undifferentiated stem cells. This could mean that the specific genetic changes in these zinc finger proteins gave an advantage to the organisms that possessed them, helping them survive and reproduce more effectively. These genetic changes may have allowed the organisms to adapt to changing environments or to develop new abilities, such as increased resistance to disease or faster growth. Undifferentiated stem cells that underwent adaptive evolution during the evolution of mammals can be identified genetically by the outcomes of positive selection on zinc finger proteins. Because of selection pressures like environmental shifts or the introduction of novel pathogens, it is plausible that some zinc finger proteins have experienced fast evolution. The emergence of novel activities or higher expression levels of these proteins as a result of this quick evolution may have given the creatures that possessed them a survival edge. Another possible outcome of positive selection in zinc finger proteins is the emergence of new genetic variations that allow for increased diversity and plasticity in stem cells. This increased diversity and plasticity could have allowed for more efficient adaptation to changing environments and could have played a role in the evolution of new organisms or new characteristics in existing organisms. Overall, the results of positive selection in zinc finger proteins can provide insight into how adaptive evolution occurred in undifferentiated stem cells during the evolution of mammals and how this evolution may have contributed to the development of new organisms and new characteristics and adaptations to changing environments.